A presença e o impacto dos movimentos relacionais intertextuais (MRI) em produções escritas do Ensino Médio: um trabalho à luz da linguística do texto - Signori, Bruno Luiz (2025)
This dissertation's main objective is to analyze the presence and impact of intertextual relational movements (MRI) in the textual productions of the Enem model essay and literary chronicle genres in Escola Básica. The research in question also focuses on the following specific objectives: (1) investigate whether there are advances in students' written production based on work with process writing; (2) verify the viability and proficiency of working with intertextuality (stricto sensu) based on the textual genres Enem model essay and literary chronicle; and (3) contribute to the teaching and learning process of textual production based on work supported by action research. In order to observe the relationship that a certain author/student establishes with the intertexts he uses, between the months of september and november 2023, reading and textual production workshops were held together with students in the third year of High School at the Colégio Estadual Professora Edna May Cardoso, school located in the city of Santa Maria (RS). During the workshops, previously approved by the UFSM Human Research Ethics Committee, we worked emphatically: with the notions of intertextuality (in the light of Text Linguistics) and MRI; and with the writing of three versions of the textual genres essay and chronicle. The texts in question were produced in the classroom and the first and second versions of both genres received guidance notes, totaling four notes per student. Theoretically-methodologically, all stages involved in this research were supported by authors such as: Bakhtin (2011, 2013) Beaugrande and Dressler (1981); Burns (1999, 2009, 2010); Dolz, Noverraz and Schneuwly (2004); Freire and Faundez (1985); Grésillon and Maingueneau (1984); Koch (2006); Koch and Elias (2022); Koch, Bentes and Cavalcante (2012), Ruiz (1998); Sá (1985), Vygotsky (1991, 2010); and White and Arndt (1991). Regarding the results, it is understood, from the analysis of the selected texts, that intertexts and intertextual relational movements can be identified in different textual genres, and that from the MRI students reacted to the recovered intertexts, qualifying their own texts based on the relationships established with intertextualities. It was also observed that the work anchored in action research and guided by the writing process helped the interaction between students and educator, helping the former to improve their writing processes. This master's level research enables the understanding that the connection between intertext and relational movement is constituted as: (i) a powerful and necessary educational resource, assisting (dialogism in) the classroom, textual production and the process of teaching and learning; and (ii) a fundamental linguistic notion, helping to understand the dialogue and relationship between texts.